Functional diversity of resilin in Arthropoda - Michels, Jan; Appel, Esther; Gorb, Stanislav N. (Beilstein Journal of Nanotechnology, 2016)
Resilin is an elastomeric protein typically occurring in exoskeletons of arthropods. It is composed of randomly orientated coiled polypeptide chains that are covalently cross-linked together at regular intervals by the two unusual amino acids dityrosine and trityrosine forming a stable network with a high degree of flexibility and mobility. As a result of its molecular prerequisites, resilin features exceptional rubber-like properties including a relatively low stiffness, a rather pronounced long-range deformability and a nearly perfect elastic recovery. Within the exoskeleton structures, resilin commonly forms composites together with other proteins and/or chitin fibres. In the last decades, numerous exoskeleton structures with large proportions of resilin and various resilin functions have been described. Today, resilin is known to be responsible for the generation of deformability and flexibility in membrane and joint systems, the storage of elastic energy in jumping and catapulting systems, the enhancement of adaptability to uneven surfaces in attachment and prey catching systems, the reduction of fatigue and damage in reproductive, folding and feeding systems and the sealing of wounds in a traumatic reproductive system. In addition, resilin is present in many compound eye lenses and is suggested to be a very suitable material for optical elements because of its transparency and amorphousness. The evolution of this remarkable functional diversity can be assumed to have only been possible because resilin exhibits a unique combination of different outstanding properties.
Keywords: biological materials; biomechanics; composites; elastomeric proteins; functional morphology

Elastomeric Proteins: Structures, Biomechanical Properties, and Biological Roles - Shewry, P. R.; Tatham, A. S.; Bailey, A. J. (Cambridge University Press, 2004)

(untitled) - Weis-Fogh, T. (J. Exp. Biol., 1960)

(untitled) - Weis-Fogh, T. (J. Mol. Biol., 1961)

(untitled) - Weis-Fogh, T. (J. Mol. Biol., 1961)

(untitled) - Andersen, S. O.; Weis-Fogh, T. (Adv. Insect Physiol., 1964)

(untitled) - Andersen, S. O. (Insect Biochem. Mol. Biol., 2010)

(untitled) - Bailey, K.; Weis-Fogh, T. (Biochim. Biophys. Acta, 1961)

Comprehensive Biochemistry - Andersen, S. O. (Resilin, 1971)

(untitled) - Schultz, R. L. (Biochim. Biophys. Acta, 1964)

(untitled) - Michels, J.; Gorb, S. N. (J. Microsc., 2012)

(untitled) - Jensen, M.; Weis-Fogh, T. (Philos. Trans. R. Soc. London, Ser. B, 1962)

(untitled) - Lyons, R. E.; Wong, D. C. C.; Kim, M.; Lekieffre, N.; Huson, M. G.; Vuocolo, T.; Merritt, D. J.; Nairn, K. M.; Dudek, D. M.; Colgrave, M. L.; Elvin, C. M. (Insect Biochem. Mol. Biol., 2011)

(untitled) - Elvin, C. M.; Carr, A. G.; Huson, M. G.; Maxwell, J. M.; Pearson, R. D.; Vuocolo, T.; Liyou, N. E.; Wong, D. C. C.; Merritt, D. J.; Dixon, N. E. (Nature, 2005)

Fuzziness - Rauscher, S.; Pomès, R. (Structural Disorder and Protein Elasticity, 2012)

(untitled) - Bennet-Clark, H. C.; Lucey, E. C. A. (J. Exp. Biol., 1967)

(untitled) - Gorb, S. N. (Arthropod Struct. Dev., 2004)

(untitled) - Burrows, M.; Shaw, S. R.; Sutton, G. P. (BMC Biol., 2008)

(untitled) - Burrows, M. (J. Exp. Biol., 2010)

(untitled) - Burrows, M. (J. Exp. Biol., 2011)

(untitled) - Burrows, M.; Sutton, G. P. (J. Exp. Biol., 2012)

(untitled) - Haas, F.; Gorb, S.; Blickhan, R. (Proc. R. Soc. London, Ser. B, 2000)

(untitled) - Haas, F.; Gorb, S.; Wootton, R. J. (Arthropod Struct. Dev., 2000)

(untitled) - Perez Goodwyn, P.; Peressadko, A.; Schwarz, H.; Kastner, V.; Gorb, S. (J. Comp. Physiol., A, 2006)

(untitled) - Gorb, S. N. (Naturwissenschaften, 1999)

(untitled) - Appel, E.; Gorb, S. N. (Bioinspiration Biomimetics, 2011)

(untitled) - Donoughe, S.; Crall, J. D.; Merz, R. A.; Combes, S. A. (J. Morphol., 2011)

(untitled) - Kannupandi, T. (Acta Histochem., 1976)

Elastomeric Proteins: Structures, Biomechanical Properties, and Biological Roles - Andersen, S. O. (Structure and Function of Resilin, 2003)

(untitled) - Michels, J.; Vogt, J.; Gorb, S. N. (Sci. Rep., 2012)

(untitled) - Michels, J.; Vogt, J.; Simon, P.; Gorb, S. N. (Zoology (Munich, Ger.), 2015)

(untitled) - Govindarajan, S.; Rajulu, G. S. (Experientia, 1974)

(untitled) - Sundara Rajulu, G. (Indian J. Exp. Biol., 1971)

(untitled) - Ramalingam, K. (Parasitology, 1973)

(untitled) - Wong, W. L.; Michels, J.; Gorb, S. N. (Parasitology, 2013)

(untitled) - Lopez-Llorca, L. V.; Fry, S. C. (Nematologica, 1989)

(untitled) - DeVore, D. P.; Gruebel, R. J. (Biochem. Biophys. Res. Commun., 1978)

(untitled) - Foerder, C. A.; Shapiro, B. M. (Proc. Natl. Acad. Sci. U. S. A., 1977)

(untitled) - Andersen, S. O. (Biochim. Biophys. Acta, 1963)

(untitled) - Andersen, S. O. (Acta Physiol. Scand., 1965)

(untitled) - Neff, D.; Frazier, S. F.; Quimby, L.; Wang, R.-T.; Zill, S. (Arthropod Struct. Dev., 2000)

(untitled) - Burrows, M.; Borycz, J. A.; Shaw, S. R.; Elvin, C. M.; Meinertzhagen, I. A. (PLoS One, 2011)

(untitled) - Wong, D. C. C.; Pearson, R. D.; Elvin, C. M.; Merritt, D. J. (Dev. Dyn., 2012)

(untitled) - Niederegger, S.; Gorb, S. (J. Insect Physiol., 2003)

(untitled) - Fujimori, E. (Biochim. Biophys. Acta, 1978)

(untitled) - Garcia-Castineiras, S.; Dillon, J.; Spector, A. (Exp. Eye Res., 1978)

(untitled) - Gast, R.; Lee, J. (Proc. Natl. Acad. Sci. U. S. A., 1978)

(untitled) - Giurginca, A.; Šustr, V.; Tajovský, K.; Giurginca, M.; Matei, I. (ZooKeys, 2015)

(untitled) - Peisker, H.; Michels, J.; Gorb, S. N. (Nat. Commun., 2013)

(untitled) - Gorb, S. N.; Filippov, A. E. (Beilstein J. Nanotechnol., 2014)

(untitled) - Gorb, S. N. (J. Morphol., 1996)

(untitled) - Edwards, H. A. (J. Exp. Biol., 1983)

(untitled) - Young, D.; Bennet-Clark, H. C. (J. Exp. Biol., 1995)

(untitled) - Bennet-Clark, H. C. (J. Exp. Biol., 1997)

(untitled) - Skals, N.; Surlykke, A. (J. Exp. Biol., 1999)

(untitled) - Raghu Varman, A. (J. Ga. Entomol. Soc., 1981)

(untitled) - Raghu Varman, A. (Experientia, 1980)

(untitled) - Raghu Varman, A.; Hermann, H. R., Jr (J. Anim. Morphol. Physiol., 1982)

(untitled) - Hepburn, H. R.; Levy, P. (J. Entomol. Soc. South. Afr., 1975)

The Insect Integument - Vincent, J. F. V. (Design for Living: The Elastic-sided Locust, 1976)

(untitled) - Hackman, R. H.; Goldberg, M. (Int. J. Parasitol., 1985)

(untitled) - Richards, A. G.; Richards, P. A. (Int. J. Insect Morphol. Embryol., 1979)

Comprehensive Insect Physiology, Biochemistry and Pharmacology - Hepburn, H. R. (Structure of the Integument, 1985)

(untitled) - Vincent, J. F. V.; Wood, S. D. E. (Nature, 1972)

(untitled) - Vincent, J. F. V. (Proc. R. Soc. London, Ser. B, 1975)

(untitled) - Vincent, J. F. V. (Tissue Cell, 1981)

(untitled) - Hackman, R. H.; Goldberg, M. (J. Insect Physiol., 1987)

(untitled) - Hackman, R. H. (J. Insect Physiol., 1975)

(untitled) - Reynolds, S. E. (J. Exp. Biol., 1975)

(untitled) - Gorb, S. N. (J. Zool., 2000)

(untitled) - Rothshild, M.; Schlein, Y.; Parker, K.; Neville, C.; Sternberg, S. (Philos. Trans. R. Soc. London, Ser. B, 1975)

(untitled) - Bennet-Clark, H. C. (J. Exp. Biol., 1975)

(untitled) - Evans, M. E. G. (J. Zool. (1965-1984), 1973)

(untitled) - Furth, D. G.; Traub, W.; Harpaz, I. (J. Exp. Zool., 1983)

(untitled) - Burrows, M. (J. Exp. Biol., 2012)

(untitled) - Gronenberg, W. (J. Comp. Physiol., A, 1996)

(untitled) - Bayley, T. G.; Sutton, G. P.; Burrows, M. (J. Exp. Biol., 2012)

(untitled) - Lehmann, F. O.; Gorb, S.; Nasir, N.; Schützner, P. (J. Exp. Biol., 2011)

(untitled) - Appel, E.; Gorb, S. N. (Zoologica, 2014)

(untitled) - Appel, E.; Heepe, L.; Lin, C.-P.; Gorb, S. N. (J. Anat., 2015)

(untitled) - Neville, A. C. (J. Exp. Biol., 1960)

(untitled) - Weis-Fogh, T. (J. Exp. Biol., 1973)

(untitled) - Gosline, J.; Lillie, M.; Carrington, E.; Guerette, P.; Ortlepp, C.; Savage, K. (Philos. Trans. R. Soc. London, Ser. B, 2002)

(untitled) - Nachtigall, W.; Wisser, A.; Eisinger, D. (J. Comp. Physiol., B, 1998)

The Functional Wing Morphology of Some Odonata - Newman, D. J. S. (University of Exeter, 1982)

(untitled) - Rajabi, H.; Ghoroubi, N.; Darvizeh, A.; Dirks, J.-H.; Appel, E.; Gorb, S. N. (Bioinspiration Biomimetics, 2015)

(untitled) - Rajabi, H.; Shafiei, A.; Darvizeh, A.; Dirks, J.-H.; Appel, E.; Gorb, S. N. (R. Soc. Open Sci., 2016)

(untitled) - Mountcastle, A. M.; Combes, S. A. (Proc. R. Soc. London, Ser. B, 2013)

(untitled) - Ma, Y.; Ning, J. G.; Ren, H. L.; Zhang, P. F.; Zhao, H. Y. (J. Exp. Biol., 2015)

(untitled) - Mountcastle, A. M.; Combes, S. A. (J. Exp. Biol., 2014)

(untitled) - Deiters, J.; Kowalczyk, W.; Seidl, T. (Biol. Open, 2016)

(untitled) - Haas, F.; Hwen, J. T. C.; Tang, H. B. (Arthropod Syst. Phylog., 2012)

(untitled) - Wootton, R. J. (Annu. Rev. Entomol., 1992)

(untitled) - Haas, F.; Beutel, R. G. (Zoology (Munich, Ger.), 2001)

(untitled) - Sun, J.; Ling, M.; Wu, W.; Bhushan, B.; Tong, J. (Int. J. Mol. Sci., 2014)

Attachment Devices of Insect Cuticle - Gorb, S. N. (Kluwer Academic Publishers, 2001)

(untitled) - Gorb, S.; Beutel, R. (Naturwissenschaften, 2001)

(untitled) - Gorb, S. N.; Beutel, R. G.; Gorb, E. V.; Jiao, Y.; Kastner, V.; Niederegger, S.; Popov, V. L.; Scherge, M.; Schwarz, U.; Vötsch, W. (Integr. Comp. Biol., 2002)

(untitled) - Creton, C.; Gorb, S. (MRS Bull., 2007)

(untitled) - Voigt, D.; Schuppert, J. M.; Dattinger, S.; Gorb, S. N. (J. Insect Physiol., 2008)

(untitled) - Hui, C.-Y.; Glassmaker, N. J.; Tang, T.; Jagota, A. (J. R. Soc., Interface, 2004)

(untitled) - Varenberg, M.; Pugno, N. M.; Gorb, S. N. (Soft Matter, 2010)

(untitled) - Filippov, A.; Popov, V. L.; Gorb, S. N. (J. Theor. Biol., 2011)

(untitled) - Borodich, F. M.; Gorb, E. V.; Gorb, S. N. (Appl. Phys. A, 2010)

(untitled) - Jagota, A.; Bennison, S. J. (Integr. Comp. Biol., 2002)

(untitled) - Spolenak, R.; Gorb, S.; Arzt, E. (Acta Biomater., 2005)

Advances in Insect Physiology: Insect Mechanics and Control - Gorb, S. N. (Smooth Attachment Devices in Insects, 2008)

Predation and Digestion in Assassin Bugs (Heteroptera, Reduviidae) - Edwards, J. S. (University of Cambridge, 1960)

(untitled) - Bennet-Clark, H. (J. Exp. Biol., 2007)

(untitled) - Bennet-Clark, H. C. (J. Exp. Biol., 1963)

(untitled) - Burrows, M. (BMC Biol., 2009)

(untitled) - Krenn, H. W. (Zoomorphology, 1990)

(untitled) - Eastham, L. E. S.; Eassa, Y. E. E. (Philos. Trans. R. Soc. London, Ser. B, 1955)

(untitled) - Hepburn, H. R. (J. Insect Physiol., 1971)

(untitled) - Betz, O.; Koerner, L.; Gorb, S. N. (Adhes. Adhes. Sealants, 2009)

(untitled) - Koerner, L.; Gorb, S. N.; Betz, O. (J. Insect Physiol., 2012)

(untitled) - Koerner, L.; Gorb, S. N.; Betz, O. (Zoology (Munich, Ger.), 2012)

(untitled) - Longhurst, A. R. (Prog. Oceanogr., 1985)

Copepod Evolution - Huys, R.; Boxshall, G. A. (The Ray Society, 1991)

(untitled) - Michels, J.; Schnack-Schiel, S. B. (Mar. Biol. (Heidelberg, Ger.), 2005)

(untitled) - Michels, J.; Gorb, S. N. (Beilstein J. Nanotechnol., 2015)

Monograph of Cimicidae (Hemiptera-Heteroptera) - Carayon, J. (Traumatic Insemination and the Paragenital System, 1966)

(untitled) - Stutt, A. D.; Siva-Jothy, M. T. (Proc. Natl. Acad. Sci. U. S. A., 2001)

(untitled) - Reinhardt, K.; Naylor, R.; Siva-Jothy, M. T. (Evolution, 2009)

(untitled) - Michels, J.; Gorb, S. N.; Reinhardt, K. (J. R. Soc., Interface, 2015)

(untitled) - Thurm, U. (Science, 1964)

(untitled) - Heusslein, R.; Gnatzy, W. (Cell Tissue Res., 1987)

(untitled) - Keil, T. A. (Microsc. Res. Tech., 1997)

Functional Surfaces in Biology - Heußlein, R.; Gras, H.; Gnatzy, W. (Functional Coupling of Cercal Filiform Hairs and Campaniform Sensilla in Crickets, 2009)

(untitled) - Sannasi, A. (Experientia, 1970)

(untitled) - Jaganathan, R.; Sundara Rajulu, G. (Indian Zool., 1979)

(untitled) - Dey, S.; Raghuvarman, A. (Indian Zool., 1983)

(untitled) - Viswanathan, S.; Varadaraj, G. (Odonatologica, 1985)